DIVERSITY OF PHYTOPLANKTON IN KSHIPRA RIVER- TRIVENI STATION, UJJAIN (M.P.) - Trivedi, Seema; karode, Anupriya (International Journal of Research -GRANTHAALAYAH, 2015)
Planktons are minute organisms and essential links in food chain in aquatic system. Plankton is most importance in the freshwater ecosystem as these are the main source of energy and having a very high nutritive value .The present study is going to centralize on kshipra river, Ujjain (M.P.) in year 2014. The plankton were collected, counted and identified by using the method suggested by APHA and Prescott. The study among all these phytoplankton Bacillariophyceae was recorded as a dominant class in Kshipra River.